Effect of terrorism on economic growth in Pakistan: an empirical analysis. Issue 1 (1st January 2019) - Zakaria, Muhammad; Jun, Wen; Ahmed, Haseeb
Abstract: The paper examines the impact of terrorism on economic growth in Pakistan. Channel variables, such as foreign direct investment (FDI), domestic investment, and government spending, through which terrorism influences economic growth, are identified. For empirical analysis, annual data for the period 1972–2014 are used, and a structural model is estimated using the generalised method of moments (GMM) estimation approach. The results reveal that (1) the impact of terrorism on FDI and domestic investment is significantly negative, whereas the impact on government spending is significantly positive and (2) the net effect of terrorism on economic growth is negative. One per cent increase in terrorism reduces FDI by 0.104 per cent, domestic investment by 0.039 per cent and economic growth by 0.002 per cent. To increase economic growth more resources must be allocated to improve law and order. To attract foreign investment, complementary domestic investment must be increased.